Acute Exercise Increases Adiponectin Levels in Abdominally Obese Men - Travis J. Saunders; Andrew Palombella; K. Ashlee McGuire; Peter M. Janiszewski; Jean-Pierre Després; Robert Ross (Journal of Nutrition and Metabolism)
Objective. To examine the effect of acute and short-term (~1 week) aerobic exercise training on plasma adiponectin levels in inactive, abdominally obese men. Materials and Methods. Inactive and abdominally obese men (n=38, waist circumference ≥102 cm) recruited from Kingston, Canada were randomly allocated to perform three bouts of aerobic treadmill exercise at either low (50% VO2 peak) or high (75% VO2 peak) intensity during a 1-week period. Blood samples were taken before and after the first exercise session and 24–72 hours following the completion of the final exercise session. Results. Adiponectin levels were elevated immediately following an acute bout of exercise at both high and low intensities (High: 5.79±0.42 versus 5.05±0.41 ug/mL; Low: 5.24±0.44 versus 4.37±0.44 ug/mL, P<0.05) and remained elevated following 30 minutes of rest. In comparison to baseline, adiponectin levels were also elevated 24–72 hours following the final exercise session (High: 5.47±0.48 versus 4.88±0.48 ug/mL; Low: 5.18±0.49 versus 4.47±0.49 ug/mL, P<0.05). Conclusion. Both acute and short-term aerobic exercise result in a significant increase in plasma adiponectin levels in inactive, abdominally obese men independent of intensity.